Pembuatan Iklan Layanan Masyarakat "Daftar Pemilih Sementara" Bawaslu Salatiga Melalui Media Sosial - Novihayani Jeane Natasya; Rr. Maria Guadalupe Sekar; Rizaldi Novalto Pradana; Muhammad Bakir; Rizki Amalia Yanuartha (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2021)
Community service carried out by the PLT team is in collaboration with Bawaslu Salatiga. Bawaslu Salatiga has a problem of lack of Human Resources in the field of Public Relations. Due to the Covid-19 pandemic, outreach activities to the community have been hampered. Based on this problem, the team then made several programs, one of which was making a public service advertisement film with the theme of the Temporary Voter List (DPS). The making of this public service advertisement is based on the theory of New Media Theory which focuses on media/facilities that utilize the internet network and digital technology as a means of interaction without being limited by space and time. so as to make the community an information society, it will be more open in thought, attitude and make us more democratic. The results of this program are in the form of videos which are then uploaded to the Youtube and Instagram accounts of the Bawaslu of Salatiga City.